Chronic bronchiolitis in ankylosing spondylitis - Marquette, David; Diot, Elisabeth; de Muret, Anne; Favelle, Olivier; Sonneville, Alain; Mammou, Saloua; Dumont, Pascal; Diot, Patrice; Marchand-Adam, sylvain (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
The pleuro-pulmonary signs of ankylosing spondylitis are generally asymptomatic, typically represented by biapical lung fibrosis. To our knowledge, the severe bronchiolitis which is sometimes observed in other spondyloarthropathies has not been described in ankylosing spondylitis. We report two cases of severe chronic bronchiolitis in ankylosing spondylitis patients. Their clinical and radiological presentation were similar, characterized by progressive deterioration of stage III-IV dyspnea, non-reversible obstructive ventilatory defect, and CT scan showing air trapping with mosaic attenuation and ground-glass opacity in expiration. Lung biopsies confirmed the diagnosis of severe follicular bronchiolitis in one patient and constrictive bronchiolitis is suspected in the other. Only the patient with follicular bronchiolitis responded positively to treatment with low doses of macrolides